Types of speech acts and principles of mother’s politeness in mother and child conversation - Silpia Rahayu (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2020)
In this study, the types of speech acts and the principles used by a mother named Fika in a conversation with her child, Nio, is investigated. The purpose of this study is to find the types and functions of a mother's speech acts when performing a communication with her child, and determine the function of the speech acts. This study employed descriptive qualitative method. The data were collected with Uninvolved Conversation Observation Technique, recording, and noting. The data obtained from the speech were in Sundanese. To analyze the data, this study used identification methods that were adapted to the theoretical foundation. The data analysis was performed using pragmatic data analysis, namely language analysis based on the pragmatic point of view. This analysis was employed to show the intention of the speaker which was expressed either explicitly or implicitly in her speech. The findings find that the dominant type of speech acts used by the mother in the conversation is assertive and the main principle is favor principle. The finding is consistent with the role of a mother as the main influencer in any child development.